Posted by So Lost on Friday, January 21, 2011 at 2:12pm.
I need to see the original problem first to help you.
why did you add 48x + 3 to equal 51x?
then the 'x' is gone in the next line?
the original problem is
3+x(12*4)-24
and I thought because by 12* 4= 48 then by adding 3 that gave me 51 then I subtracted 24 and that left me with 27 so I divided 48 by 27 and that gave me 1.7 so i placed 1.7 as the x and it's on the other line showing how the steps are broken down. I didn't think it would be correct doing it straight across.
3 + x(12*4) - 24
if that is the problem then,
3 + 48x - 24
48x - 21
48x = 21
x = 21/48
x = 7/16
you can only combine 'like terms'
x terms can only be added to other x terms, constant terms can only be added to other constant terms.
do you understand?
no I don't because I was going by pemdas.
what is 'pemdas'?
Parenthesis, Exponents, Multiply, Divide, Add, Subtract (order of operations for evaluating math expressions)
I followed that
3 + x(12*4) = 24
multiply 12*4
3 + 48x = 24
subtract 3 from both sides
3 - 3 + 48x = 24 - 3
48x = 21
divide both sides by 48
48x/48 = 21/48
x = 21/48
reduce fraction
x = 7/16
thank you